Azithromycin in Periodontal Therapy: Beyond the Antibiotics - Singh, Vijendra Pal; Nayak, Sangeeta Umesh; Nettemu, Sunil Kumar; Nettem, Sowmya; Lee, Yen Hui; Verma, Madhu B. (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Periodontitis is a multifactorial disease, in which microorganisms in plaque biofilm play a major role. Scaling and root planing is the primary mode of non-surgical treatment for periodontal disease. Adjunctive use of an antimicrobial is advocated in certain periodontal disease conditions. Azithromycin might be considered a promising adjunctive drug in the treatment for periodontal disease because of its distinguished characteristic of immunomodulation, anti-inflammatory and antibiotic property along with the accumulation in higher concentration into the acute reactant cells and sustained release at the site of infection. This antibiotic is popular for its very simple dosage regime and limited side effects. The objective of this literature review to highlight the mechanism and potential favourable role in the management of various form of the periodontal disease.